Seagrasses benefit from mild anthropogenic nutrient additions - Vieira, Vasco M. N. C. S.; Lobo-Arteaga, Jorge; Santos, Rafael; Leitão-Silva, David; Veronez, Arthur; Neves, Joana M.; Nogueira, Marta; Creed, Joel C.; Bertelli, Chiara M.; Samper-Villarreal, Jimena; Pettersen, Mats R. S. (Frontiers in Marine Science, 2022)
Seagrasses are declining globally, in large part due to increased anthropogenic coastal nutrient loads that enhance smothering by macroalgae, attenuate light and are toxic when in excessive concentrations of inorganic nitrogen and phosphorus. However, as sanitation is improved many seagrass meadows have been observed to recover, with a few studies suggesting that they may even benefit from mild anthropogenic nutrient additions. Monitoring seagrass demography and health has faced difficulties in establishing the adequate variables and metrics. Such uncertainty in the methods has caused uncertainty of the significance of results presented and compromised extrapolations to other seasons, areas or species. One solution has come from within the plant self-thinning theories. During the 1980’s, an Interspecific Boundary Line (IBL) was determined as the upper limit of the combination of plant density and above-ground biomass for any stand on Earth, setting their maximum possible efficiency in space occupation. Recently, two meta-analyses to determine specific IBLs for algae and for seagrasses have been performed. The recently updated seagrass dataset comprises 5052 observations from 78 studies on 18 species. These IBLs opened new perspectives for monitoring: the observed distance of a stand to the respective IBL (i.e., each stand’s relative efficiency of space occupation) were demonstrated to be a valuable indicator of a population’s health. Thus, this metric can be used to determine the impact of nutrients and pollutants on algae and seagrass populations. Furthermore, because the IBLs are common to all species, they may be used to compare all species from any location worldwide. This novel approach showed that Halodule wrightii, Halodule beaudettei, Halophila baillonii, Zostera marina and Zostera noltei meadows benefit from anthropogenic additions of nitrogen and phosphorus, as long as these additions are moderate. In fact, the healthier Z. noltei meadows in Portugal (and among the healtiest meadows worldwide), were the ones exposed to effluents from Waste Water Treatment Plants (WWTP) and a food factory. We conclude that those effluents are providing water with enough quality, and that their optimal management should coordinate the technological solutions of the WWTP with the natural potential of seagrass meadows as water purifiers and biomass producers.